2010
DOI: 10.1186/1472-6793-10-19
|View full text |Cite
|
Sign up to set email alerts
|

Identification of differences in human and great ape phytanic acid metabolism that could influence gene expression profiles and physiological functions

Abstract: BackgroundIt has been proposed that anatomical differences in human and great ape guts arose in response to species-specific diets and energy demands. To investigate functional genomic consequences of these differences, we compared their physiological levels of phytanic acid, a branched chain fatty acid that can be derived from the microbial degradation of chlorophyll in ruminant guts. Humans who accumulate large stores of phytanic acid commonly develop cerebellar ataxia, peripheral polyneuropathy, and retinit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
33
1
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(38 citation statements)
references
References 88 publications
(115 reference statements)
3
33
1
1
Order By: Relevance
“…While there are known functional differences between macaque and rodent peroxisomes (Hoivik et al 2004), comparative data from dogs suggested that those differences are likely explained by derived changes in rodents, not primates (Foxworthy et al 1990). Differences have also been observed in peroxisomal gene functioning and peroxisomal lipid metabolism between apes or humans and other primates (Somel et al 2008;Keebaugh and Thomas 2010;Watkins et al 2010). In contrast, our results suggest a different, major biological distinction in the regulation of peroxisomerelated genes between all primates and other mammals, possibly driven by adaptive events that occurred in the ancestral primate lineage.…”
Section: Comparative Primate Genomicscontrasting
confidence: 37%
“…While there are known functional differences between macaque and rodent peroxisomes (Hoivik et al 2004), comparative data from dogs suggested that those differences are likely explained by derived changes in rodents, not primates (Foxworthy et al 1990). Differences have also been observed in peroxisomal gene functioning and peroxisomal lipid metabolism between apes or humans and other primates (Somel et al 2008;Keebaugh and Thomas 2010;Watkins et al 2010). In contrast, our results suggest a different, major biological distinction in the regulation of peroxisomerelated genes between all primates and other mammals, possibly driven by adaptive events that occurred in the ancestral primate lineage.…”
Section: Comparative Primate Genomicscontrasting
confidence: 37%
“…Она находится в жирах жвачных животных, молоч-ных продуктах и некоторых сортах рыбы [39]. Таким образом, повышение уровня фитановой кислоты в плазме можно устранить с помощью диетического ограничения [39].…”
Section: генетическое исследованиеunclassified
“…PA can be obtained as RBC bound stuff (Watkins et al, 2010), which could serve as a biomarker for evaluating digestive health (Moser et al, 2013) and influence the functions of nervous, cardiovascular, and skeletal systems in human and great apes (Watkins et al, 2010).…”
Section: Metabolism Profile In Human And/or Other Animalsmentioning
confidence: 99%
“…However, Gloerich et al (2007) demonstrated that peroxisome proliferator-activated receptor-alpha (PPARα) is responsible for PYT metabolism to PA in mice (Watkins et al, 2010). Ruminants and great captive apes/cohort of humans (e.g.…”
Section: Metabolism Profile In Human And/or Other Animalsmentioning
confidence: 99%